2018
DOI: 10.3389/fcvm.2018.00021
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Pathophysiology of Calcific Aortic Valve Disease Propose Novel Molecular Therapeutic Targets

Abstract: Calcific Aortic Valve Disease (CAVD) is the most common heart valve disease and its incidence is expected to rise with aging population. No medical treatment so far has shown slowing progression of CAVD progression. Surgery remains to this day the only way to treat it. Effective drug therapy can only be achieved through a better insight into the pathogenic mechanisms underlying CAVD. The cellular and molecular events leading to leaflets calcification are complex. Upon endothelium cell damage, oxidized LDLs tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
51
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 106 publications
1
51
0
5
Order By: Relevance
“…AVICs are the predominant cells in aortic valve leaflets and play an important role in maintaining valvular homeostasis. In the pathological condition of CAVD, however, AVICs synthesize and secret ECM proteins, cytokines and growth factors and thus become key cells involved in valvular inflammation [42]. However, the mechanism by which AVICs adapt a proinflammatory phenotype remains unclear [43].…”
Section: Discussionmentioning
confidence: 99%
“…AVICs are the predominant cells in aortic valve leaflets and play an important role in maintaining valvular homeostasis. In the pathological condition of CAVD, however, AVICs synthesize and secret ECM proteins, cytokines and growth factors and thus become key cells involved in valvular inflammation [42]. However, the mechanism by which AVICs adapt a proinflammatory phenotype remains unclear [43].…”
Section: Discussionmentioning
confidence: 99%
“…Согласно мнению западных исследователей, в большинстве случаев развитие КБАК у взрослых являлось результатом идиопатической кальцификации и дистрофических изменений нормального клапана, либо было следствием ревматического поражения клапана, либо кальцификации и фиброза врожденного двустворчатого АК [6]. В 90-х годах было доказано, что клапанный кальциноз представляет собой активный патологический процесс, включающий хроническое воспаление, липидную инфильтрацию [7], образование кальциевых депозитов, активацию ренин-ангиотензиновой системы [8]. В наши дни не теряют своей актуальности все приведенные выше теории формирования КБАК.…”
unclassified
“…In histological materials, it can be found that the superoxide in the stenotic valves is around the calcification zones. The key role in the development of aortic valve stenosis is played by "uncoupled" NOS and not by NADPH; see Figure 1 Inflammatory cytokines, TNF-a and IL-6 reduce the release of NOS (Hulin et al, 2018). TNF-a causes loss of the protective function of the valvular interstitial cells, chronic inflammation, and osteogenic activation by reducing SOD and tetrahydrobiopterin (BH4) (Farrar et al, 2015).…”
Section: Matrix Metalloproteinases (Mmp) and Tissue Inhibitors Of Metmentioning
confidence: 99%